Performance Enhancement Of Mobile IPv6 Client Using Anycast With Multi-Mirror Servers - Neoh, Kee Lin (2008)
In this thesis, an active anycast server selection model is proposed to enable roaming mobile client to detect and access a nearer and better server based on mobile client's latest network location, without requiring additional server or requiring the servers to perform server handoffs and client location tracking.